Ceratiocaris from the Silurian Waukesha Biota, Wisconsin. (9th May 2016) - Jones, Wade T.; Feldmann, Rodney M.; Schweitzer, Carrie E.
Abstract: Phyllocarids of the Waukesha Biota were systematically and taphonomically evaluated. Three Ceratiocaris species are present in the biota: C. macroura Collette and Rudkin, 2010; C. papilio Salter in Murchison, 1859; and C. pusilla Matthew, 1889. Specimens range in completeness from nearly complete, including the cephalic to caudal regions, to isolated telsons and furcae. Evidence of Salter's position is present in only three specimens. Relatively complete specimens are interpreted to represent corpses, rather than molts; whereas specimens including only the pleon and caudal region, or caudal region, and specimens with evidence of Salter's position likely represent exuviae. Specimens are preserved essentially as compression fossils exhibiting two types of preserved cuticle: brown inner cuticle, which tends to be impressed over the topography of bedding planes on which specimens are preserved, and blue-gray phosphatized cuticle exhibiting sub-millimeter scale relief. Cuticle phosphatization likely occurred during early diagenesis. The presence of characteristic near-shore species and C. pusilla, only known from turbidite facies, interpreted to possibly represent a marine trough, suggests that the Waukesha phyllocarid assemblage might represent a transported assemblage, rather than a biota, or that C. pusilla from the Jones Creek Formation was transported basinward in sediment gravity flows.